Анализ металлургического сырья и вспомогательных материалов черной металлургии - Степин В. В. Василий Васильевич; Федорова Н. Д. Нина Дмитриевна; Курбатова В. И. Вера Ивановна; Камаева Л. В. Людмила Витальевна; Сташкова Н. В. Наталья Владимировна (Москва, Металлургия, 1982)
Авт. указаны на обороте тит. л.